(untitled) (Journal of the College of Education for Women, 2019)
This study aims to study the inherited occupations which are considered to be a cultural, civilized and social legacy that effected by the Prevailing social and economic circumstances in the Iraqi society .The study aimed to achieve several goals, including:Identify the relationship between the urbanization and inherited occupations in the old city Al-Karkh.Identify the relationship between the ecological construction and inherited occupations in the old city Al-Karkh.Recognize the factors and motives inherited occupations in the study area .Identify the role of inherited occupations in promoting opportunities cohesion of the family system in the study area.The field of the study had concentrated on a sample of families which are working in the inherited occupations, the samples were 300 families that had been choose by the intentional method of choosing samples, and also 10 Respondents as model to the case study .The study used a combination of statistical methods to achieve the objectives of the study.Most important results that recommendation are:Housing near the work place of the most important factors contributing to the inheritance of professions .Most of the Respondents confirmed that the inherited occupations Contribute to the cohesion of the family system .Most of the Respondents confirmed that the respect for the opinions of the family members if the occupations manners is the main reasonin the cohesion of the family.The most important recommendations of the study are:A recommendation to the responsible authorities to grant licenses and facilities for professional occupations popular culture and organization of the mechanisms of action in order to achieve growth opportunities for the local community.To activate the role of social workers to monitor the problems and obstacles workers inherited occupations and problems of their families and their working conditions.A recommendation to the competent authorities to organize courses and conferences that contribute to the development of scientific research in the field of study of local communities as to contribute in their development.The letter also included a set of proposals that contribute to the development enhancing the developmental advancement opportunities for careers legacy and the community.